Commodities in Unequal Exchange: Global Price Formation and Indonesia’s RBD Coconut Oil Exports - Sarah Diba; Tavi Supriana; Iskandarini Iskandarini (Universitas Pattimura, 2026)
This study investigates the determinants of Indonesia’s Refined, Bleached, and Deodorized Coconut Oil (RBD CNO) export volume through the lens of unequal exchange and global price formation. Using panel data from seven major destination countries—China, the United States, Sri Lanka, South Korea, Russia, Singapore, and Malaysia—over the period 2014–2023, the analysis estimates Common Effect, Fixed Effect, and Random Effect models, with model selection based on the Chow, Hausman, and Lagrange Multiplier tests. The results indicate that international RBD CNO prices exert a negative and statistically significant effect on export volume, while the GDP of importing countries has a positive and significant influence. In contrast, population size and Indonesia’s domestic production capacity show no significant effects. These findings suggest that export performance is shaped more by external market structures and purchasing power asymmetries than by domestic supply conditions. The study’s novelty lies in integrating panel econometric analysis with a political economy perspective, demonstrating how Indonesia’s position as a primary commodity exporter entails structural vulnerability to global price volatility. The findings contribute to sociological debates on trade dependency and unequal exchange, highlighting how asymmetric market relations constrain export growth in the Global South.